3‐Deazaneplanocin A and Neplanocin A Analogues and Their Effects on Apoptotic Cell Death. Issue 1 (15th October 2014) - Tam, Eric K. W.; Nguyen, Tuan Minh; Lim, Cheryl Z. H.; Lee, Puay Leng; Li, Zhimei; Jiang, Xia; Santhanakrishnan, Sridhar; Tan, Tiong Wei; Goh, Yi Ling; Wong, Sze Yue; Yang, Haiyan; Ong, Esther H. Q.; et al.
Abstract 3‐Deazaneplanocin A (DzNep) is a potential epigenetic drug for the treatment of various cancers. DzNep has been reported to deplete histone methylations, including oncogenic EZH2 complex, giving rise to epigenetic modifications that reactivate many silenced tumor suppressors in cancer cells. Despite its promise as an anticancer drug, little is known about the structure–activity relationships of DzNep in the context of epigenetic modifications and apoptosis induction. In this study, a number of analogues of DzNep were examined for DzNep‐like ability to induce synergistic apoptosis in cancer cells in combination with trichostatin A, a known histone deacetylase (HDAC) inhibitor. The structure–activity relationship data thus obtained provide valuable information on the structural requirements for biological activity. The studies identified three compounds that show similar activities to DzNep. Two of these compounds show good pharmacokinetics and safety profiles. Attempts to correlate the observed synergistic apoptotic activities with measured S‐adenosylhomocysteine hydrolase (SAHH) inhibitory activities suggest that the apoptotic activity of DzNep might not be directly due to its inhibition of SAHH.